Arms trade, security and conflict - Levine, Paul; Smith, Ron (London ; New York : Routledge, 2003)
An area of huge concern to many people around the world, the economics of the Arms Industry are a vital strand that needs to be understood. This volume brings together contributors from all over the globe and focuses on this important area.
This conference volume contains a set of papers given at the June 1999 conference at Middlesex University Business School on the arms trade security and conflict.
Includes bibliographical references and index.
rpm 20/09/16
Loans
Keywords: Arms transfers; Defense industries; National security